Diversity in clinical isolates of Ictalurid herpesvirus 1 (IcHV1) from U.S. farm-raised catfish and virulence assessment in channel and channel × blue catfish hybrids - Venugopalan, Arun (Journal of fish diseases, 2024)
© 2024 John Wiley & Sons Ltd.